2011
DOI: 10.1016/j.juro.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Results of Vardenafil Mediated Power Doppler Ultrasound, Contrast Enhanced Ultrasound and Systematic Random Biopsies to Detect Prostate Cancer

Abstract: Vardenafil enhanced power Doppler ultrasound enables excellent visualization of the microvasculature associated with cancer and can improve the detection rate compared to contrast enhanced power Doppler ultrasound and the random technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Enhanced ultrasound techniques including color and power Doppler have been used in an attempt to enhance prostate cancer detection over conventional TRUS (LoTRUS). However, despite modest improvements over LoTRUS these modalities are not in widespread clinical use despite availability [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced ultrasound techniques including color and power Doppler have been used in an attempt to enhance prostate cancer detection over conventional TRUS (LoTRUS). However, despite modest improvements over LoTRUS these modalities are not in widespread clinical use despite availability [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Tadalafil suppressed the decrease in bladder blood flow and impairment of bladder function in a rat partial bladder outlet obstruction model . In humans also, a single administration of PDE5 inhibitors, sildenafil, valdenafil and tadalafil, significantly increased prostate blood flow detected by power Doppler ultrasound in patients with BPH, patients with prostate‐specific antigen level of >4 ng/mL and healthy individuals . Zaparinst, a PDE5 inhibitor, enhanced NO‐induced vasodilation in isolated rat aortic rings, pulmonary circulation of intact lambs and cats with experimental pulmonary hypertension, and in cats’ hindlimb circulation .…”
Section: Pde5 and Vascular Functionmentioning
confidence: 96%
“…[26] This finding was consistent with the results of several TRUS biopsy controlled studies with reported CEUS sensitivity ranging from 65–93%. [2224;27] In his phase I FT trial of 12 patients using a diode laser as the ablative energy source, Lindner et al creatively employed CEUS to monitor ablative areas, which appeared as well-defined regions of decreased enhancement. Post-treatment MRI confirmed good overlap of necrotic areas with intraoperative CEUS findings.…”
Section: Ultrasound Guidance In Focal Therapy Of Prostate Cancermentioning
confidence: 99%